Motor elements of the third month variously predict individual later motor elements - Gajewska, Ewa; Moczko, Jerzy; Sobieska, Magdalena (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study aims to determine the correlations between axial and distal motor features observed at 3 months of age on later motor elements at 4–5 and 7–8 months.Materials and methodsWe analyzed 93 children (50 boys); 24 were born prematurely. All children underwent a prospective qualitative evaluation of motor development, performed by the physiotherapist, at 3, 4–5, and 7–8 months of age. We analyzed infants’ motor development in the third month using the validated Quantitative and Qualitative Assessment of Motor Development Worksheet. The qualitative assessment determined for 4–5 and 7–8 months was based on the Vojta development concept.ResultsStudies showed that axial features observed in the third month significantly and relatively strongly correlated (Cramer’s V = 0.4–0.6) with proper asymmetric elbow support. In the supine position, crossing the body’s midline and grasping correlated relatively strongly with the correct positioning of the pelvis and lower limbs observed in the third month. The axial and distal elements from the third month remain necessary to achieve a qualitatively correct oblique sitting position at 7–8 months. The relatively high values of Cramer’s V were also confirmed by the relatively high values of the Tau test. At 7–8 months, this relationship was quite strong sometimes (high Cramer’s V) but applied to a minor part of the variability (low Tau).ConclusionAxial elements observed at 3 months of age correlate relatively strongly with axial elements at 4–5 months. The relationships between the elements at 3 months of age and those studied at 7–8 months were moderate but related to axial and distal features. Without proper spine functioning, the development of the shoulders and pelvis will not occur properly. Findings support the early use of axial motor features as developmental indicators for motor progression, with implications for early intervention programs.